Effects of environmental factors on phosphorus adsorption capacity and release risk in lake sediments - Yan Jiang; Xiulan Ma; Bo Wang; Bingbing Jiang; Weikai Wang; Yujun Wang; Chendong Zhang (Plant, Soil and Environment, 2022)
Sediment is an important part of the lake and reservoir ecosystem, and also an important "source" and "sink" of pollutants. In this paper, sediment A (Xinlicheng Reservoir Sediments), sediment B (eutrophic lake reservoir sediments) and soil C (topsoil at the inflow of Yitong River near Xinlicheng Reservoir) are used as research objects, and batch experiments are used to study the adsorption capacity and release risk of phosphorus (P). The results showed that the maximum adsorption capacity of the adsorbent for phosphorus accounted for 91.51-99.63% of the total adsorption capacity within 0-120 min; when the background liquid phosphorus concentration is lower, soil and sediment all have different degrees of phosphorus release. By this time soil and sediment is the "source" of pollutants; when the phosphorus concentration is 10 mg/L, the maximum adsorption capacity is 116.19-428.91 mg/kg, and the adsorption capacity of sediment A is 2.41 times and that of soil C and sediment B, respectively. 3.69 times, indicating that if phosphorus enters the water body from the soil due to surface runoff and other factors, the sediment has a strong adsorption capacity for phosphorus, that is, soil and sediment is an effective "sink" of phosphorus; the Henry equation is used to fit the P adsorption isotherm effect. Preferably, and r is greater than 0.968. The amount of phosphorus absorbed by sediment A and sediment B is affected by pH higher than that of soil C. When the value of pH is 7, the adsorption amount is the largest; the P induced lake eutrophication risk index (ERI) of sediment A, sediment B and soil C is sediment B > soil C > sediment A. As the temperature of sediment and soil rises, the ERI index of phosphorus gradually decreases.